SIMULASI MONTE CARLO DALAM OPTIMASI BIAYA PEMELIHARAAN - Wilson Kosasih; Iphov Kumala Sriwana; Winda Jeania Purnama (Jurnal Ilmiah Teknik Industri, 2021)
Unplanned maintenance can result in high costs. This study uses a Monte Carlo simulation to minimize maintenance costs, where the failure cost and the preventive cost can be balanced. This research was conducted in a medium-sized company that produces shoe soles. The object of research is focused on the critical components of a rotary injection molding machine. The research data is obtained from the company's factual data in the form of historical machine breakdowns, labor costs, component costs, and production loss costs. The results demonstrate that the optimal preventive maintenance schedule can save the rate of maintenance costs for each critical component by 24.54%, 54.63%, and 21.51% compared to actual maintenance.